(untitled) (Research, Society and Development, 2022)
Objective: to analyze the general recommendations for the practice of breastfeeding in the face of infection by the new coronavirus. Method: integrative literature review, carried out in the LILACS and Pubmed databases, from March to May 2020. The searches took place with the following combinations of descriptors “Coronavirus”, “Lactation” and “Breastfeeding”. The limitation regarding the year of publication of the articles during the searches carried out was from 2019 to 2020. Results: the search in the data sources allowed the inclusion of ten articles, two from Brazilian journals, found in the LILACS database, and eight of international origin, selected in the PubMed database. Conclusion: From this review, it became evident that most studies addressed the recommendation to maintain the practice of breastfeeding in women with COVID-19. These studies reinforce the importance of counseling, the necessary care during the act of breastfeeding, in addition to recognizing the benefits of breastfeeding. The large number of research on the subject defends and favors breastfeeding for women suspected or diagnosed with COVID-19, which limits the discussion with similar articles.